Ethics of sexual and loving relationships - López Sánchez, Félix (2017)
The present article proposes ethical bases that should support the amorous and sexual relations of the people. This is based on respect for the principles of freedom, dignity and equality between the members of the couple. The proposal is supplemented by general and specific procedures for applying these principles, which focus on the ethics of consent and equality.For the construction of an ethics of consent, a Program is offered that seeks to develop certain competences based on didactic units that contain objectives and contents, as well as activities and forms of evaluation.